Comparative Analysis of the State Speeches of President Susilo Bambang Yudhoyono and Joko Widodo using the Aristotelian perspective - Slamet Amin Aminuddin (Journal of Governance and Public Policy, 2022)
This study aims to compare the rhetoric of SBY & Jokowi's state speeches during the administration of President Susilo Bambang Yudhoyono in the first period between 2009 and 2014 and President Joko Widodo in the first period, namely between 2014 and 2019 using Aristotle's rhetorical perspective. This study uses a qualitative method approach. The data sources in this study were taken from SBY's state speech (2009-2014) and 498 Jokowi dodo citizenship speeches (2014-2019) which were published in national ceremonies. The findings in this study indicate that SBY combines deliberative and forensic rhetoric in delivering his speech, while Jokowi consistently uses deliberative rhetoric in each theme. In maintaining executive-legislative relations, Jokowi's political communication style seems to be more effective than SBY's, but in maintaining relations within the executive, especially in the cabinet. SBY is more effective.